NILAI EKONOMI WISATA GUNUNG SIBAYAK BERDASARKAN METODE BIAYA PERJALANAN (Travel Cost Methode) DI BERASTAGI SUMATERA UTARA - Br Brahmana1, DwiDamiaty BrahmiPutri; Yoza, Defri; Budiani, Evi Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Natural tourism consists object and recreational tourism which related any activities that explores the potential of natural resources and its ecosystems. One of the places which required it is Berastagi, Tanah Karo in North Sumatera. The freshness and coolness of Berastagi atmosphere attracts many tourists to visit it. One of the attraction in Berastagi is the famous Mount Sibayak which is still developing until today. The purpose of this research is find out the characteristic of visitors who came for recreation to Sibayak Mountain, to knowÂ  how much economic value tour of Sibayak Mountain per year based on Travel Cost Methode (TCM), to find out the factors affecting of economic value based on Travel Cost Methode (TCM). Materials and objects of this research is questionnaire sheet. Data collected using SPSS 21 (Statistic Package For Social Science) analyze. The results showed that Sibayak Mountain economic value based on Travel Cost Methode (TCM) of Rp.3.926.520.145,6/ year, with average person of Rp. 103.438,36.Â Keywords : Economic Value , Cost Travel, Sibayak Mountain